2003
DOI: 10.1073/pnas.2333806100
|View full text |Cite
|
Sign up to set email alerts
|

Base pair analogs in the gas phase

Abstract: A rotationally resolved electronic spectrum of the gas-phase dimer 2-aminopyridine⅐2-pyridone, an analog of the adenine⅐thymine base pair, has been observed and assigned, leading to precise measurements of its moments of inertia and preliminary determinations of its structure. A Watson-Crick configuration results, with N⅐⅐⅐HON and NOH⅐⅐⅐O hydrogen bond lengths of 2.898 and 2.810 Å, respectively. The two bases are found not to be coplanar; a dihedral angle of 6.1°between the base planes is also estimated from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 25 publications
1
44
0
Order By: Relevance
“…For example, the angle between the planes of paired adenine and thymine, which can be extracted from the buckle and propeller angles, is remarkably similar to the dihedral angle estimated from the measured moments of inertia of 2-aminopyridine·2-pyridone, an analog of the A·T base pair, in the gas phase, i.e ., 6.7° predicted vs . 6.1° found experimentally (Roscioli and Pratt 2003). The predicted length of the A(N1)···T(H3)–T(N3) hydrogen bond also closely matches the value found in the same experiment, i.e ., 2.87 Å computed vs .…”
Section: Sequence-dependent Structure and Deformationsupporting
confidence: 53%
“…For example, the angle between the planes of paired adenine and thymine, which can be extracted from the buckle and propeller angles, is remarkably similar to the dihedral angle estimated from the measured moments of inertia of 2-aminopyridine·2-pyridone, an analog of the A·T base pair, in the gas phase, i.e ., 6.7° predicted vs . 6.1° found experimentally (Roscioli and Pratt 2003). The predicted length of the A(N1)···T(H3)–T(N3) hydrogen bond also closely matches the value found in the same experiment, i.e ., 2.87 Å computed vs .…”
Section: Sequence-dependent Structure and Deformationsupporting
confidence: 53%
“…1–6 In conventional hydrogen bonds, X – H · · · A , a hydrogen atom bridges the proton donor X and proton acceptor A. The donor is usually very electronegative, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, 2-aminopyridine ͑AP͒ dimer, see Scheme 1, is probably the most widely used model for investigating basic photochemical reaction mechanisms. [5][6][7][8][9] This dimer consists of the N-H donor and the aromatic N acceptor group of the single base and is also of doubly hydrogen-bonded structure. Earlier theoretical studies on one-dimensional potential-energy surfaces of excited-states in the 2-AP dimer 7 have shown that a conical intersection between a local excited-state ͑LE͒ and a charge transfer ͑CT͒ state along a proton-transfer coordinate was responsible for the deactivation of the 2-AP dimer in vacuum.…”
Section: Introductionmentioning
confidence: 99%